INTERSECTİONAL (α,A)-SOFT NEW-İDEALS İN PU-ALGEBRAS - Samy Mohammed Mostafa; Fatema Faisal Kareem; Hussein Ali Jad (Journal of New Theory)
The new notions, intersectional A-soft new-ideals and intersectional (a,A)-soft new-ideals in PU-algebras are introduced and their properties are investigated. The relations between an intersectional Asoft new-ideals and an intersectional a,A)-soft new-ideals are provided. The homomorphic image of an intersectional (a,A)-soft new-ideals is studied